Socioeconomic deprivation and the outcome of pulmonary rehabilitation in England and Wales. Issue 6 (11th January 2017) - Steiner, Michael C; Lowe, Derek; Beckford, Katy; Blakey, John; Bolton, Charlotte E; Elkin, Sarah; Man, William D -C; Roberts, C Michael; Sewell, Louise; Walker, Paul; Singh, Sally J
Abstract : Background: Pulmonary rehabilitation (PR) improves exercise capacity and health status in patients with COPD, but many patients assessed for PR do not complete therapy. It is unknown whether socioeconomic deprivation associates with rates of completion of PR or the magnitude of clinical benefits bequeathed by PR. Methods: PR services across England and Wales enrolled patients to the National PR audit in 2015. Deprivation was assessed using Index of Multiple Deprivation (IMD) derived from postcodes. Study outcomes were completion of therapy and change in measures of exercise performance and health status. Univariate and multivariate analyses investigated associations between IMD and these outcomes. Results: 210 PR programmes enrolled 7413 patients. Compared with the general population, the PR sample lived in relatively deprived neighbourhoods. There was a statistically significant association between rates of completion of PR and quintile of deprivation (70% in the least and 50% in the most deprived quintiles). After baseline adjustments, the risk ratio (95% CI) for patients in the most deprived relative to the least deprived quintile was 0.79 (0.73 to 0.85), p<0.001. After baseline adjustments, IMD was not significantly associated with improvements in exercise performance and health status. Conclusions: In a large national dataset, we have shown that patients living in more deprived areas are less likely to complete PR. However, deprivation was not associated with clinical outcomes in patients who complete therapy. Interventions targeted at enhancing referral, uptake and completion of PR among patients living in deprived areas could reduce morbidity and healthcare costs in such hard-to-reach populations.